Early guidance and interception of developing Class III in primary dentition: A case series with 10 years follow up - Aditi Kapur; Rigzin Tamchos; Raj Kumar Verma (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2025)
Skepticism about the long-term stability of immediate results achieved due to ongoing changes in craniofacial structures till growth completion is perhaps one of the reasons why very early treatment of Class III malocclusion is often not considered by many clinicians. This paper highlights the positive growth changes in the long-term, post-correction, in different types of developing Class III relations in children aged 2–5 years. The favorable outcomes may urge a more significant number of pediatric dentists to undertake this initiative for the benefit of young child patients and the orthodontists to guide timely referrals.